Relações de poder em território de segregação e conflito: representações que engendram territorialidades. Estudo de caso: da Vila Nossa Senhora Aparecida no contexto da Montanha Russa - Santa Maria/RS. - Azevedo, Carla Juny Soares de (2010)
The present work research-participant uses the conception of social geography support and assume as discussion and analysis object the power relations established from the weakness of the right to territory, as a producer of socio-spatial segregation. For this analysis I focus on the actors' statements and representations raised in the midst of the investigative process, which was established from the pursuit of knowing, along with the residents, the plans of the Municipality for the territory represented by the Montanha Russa and more particularly for the Vila Nossa Senhora Aparecida, at that particular time in which they plan to deploy the Parque Municipal da Barragem do rio Vacacaí or DNOS, Santa Maria, Rio Grande do Sul. As part of environmental conflict, irregular land can also be seen as one of the issues underlying the processes that produce the territoriality of Vila Nossa Senhora Aparecida and the extent that restrict access to other citizenship rights, the land irregularity participates in the production of basic socio-spatial segregation. The lack of transparency plans that are based on the municipal level, motivates diligence that occurs with the residents, enabling these actors access to information, documents, maps, and contact with different actors that contribute to a broader perception of the facts, fostering an atmosphere of seeking understanding and uncovering the hidden interests. Such practices indicate the possibility of greater participation of these actors, a negotiated alternative to the situation, as well as the emergence of renewed representation processes, production and reproduction of place.